Cytotoxic activity assay of tinocrisposide from tinospora crispa on human cancer cells - Adnan, Adek Zamrud; Bakhtiar, Muhammad Taher; Afriani, Tika; Roesma, Dewi Imelda; Putra, Andani Eka (Scholars Research Library, 2016)
Tinospora crispa is a climber plant belonging to the family of Menispermaceae. This plant has been used traditionally in Indonesia to treat some diseases and conditions such as fever, malaria, rheumatism, diabetes, cholera and inflammation. The aims of this study was to investigate cytotoxic activity of tinocrisposide extracted from the plant against human cancer cell lines. Cytotoxic activity of tinocrisposide in interval dose of 100; 50; 25; 12.5; 6.25; 3.125 μg/mL has been investigated on H1299 and MCF-7 cell lines and their effects were quantified spectrophotometrically with the 3-(4,5 dimethylthiazol-2-yl)2,5-diphenyl tetrazolium bromide (MTT) assay at wavelength, λ 570 nm. Tinocrisposide in concentrations of 100; 50; 25; 12.5; 6.25; 3.125 μg/mL has been treated against H1299 cell line and showed a percentage viability of 55.5; 67.70; 80.84; 81.09; 82.69; and 87.06% respectively, with IC50 70.9 μg/mL, whereas on MCF-7 cell line showed percentage viability of 80.71; 89.30; 92.76; 96.01; 96.58, and 102.66% respectively, with IC50 > 100 μg/mL. It can be concluded that tinocrisposide has not shown any cytotoxic activity against H1299 and MCF-7 cell line, but it can be used as a chemopreventive agent toward those cell lines.